Role of resilience in selection of R factors for an RC building - Prasanth, S.; Ghosh, Goutam (Frontiers in Built Environment, 2022)
In the seismic design of a reinforced concrete building, selecting appropriate response reduction factor (R) is vital for the building’s seismic response. Indian Standard (IS) 1893-2016 provides R values of 3 and 5 for ordinary moment resisting frames and special moment resisting frames, respectively. As R factors are used to incorporate the building’s non-linearity, R factor selection should be based on the building’s performance in terms of resilience. Since IS does not provide any clause on the background for selecting R factors for the design aspects, the study emphasizes the appropriate selection of R factors with respect to a building’s functionality, performance level, and resilience. In this study, a high-rise building was designed with various R factors (R = 3, 4, 5, and 6). To estimate the building’s functionality, five different recovery paths (RP-1 to RP-5), which match the real scenario, were used. The response of the building in each case was observed at two design levels, Design Basic Earthquake (DBE) level and MCE level. Variations in ductility demand, performance level, and resilience for each building case at each design level were observed. The R factor was used to obtain lateral design force at the DBE level by reducing the actual base shear placed on the structure. The reduction in the lateral design force with maximum R yielded high ductility demand and high loss of resilience. The result shows that the considered building can be designed with a maximum R of 6 since its resilience is almost 50%; hence, recovery is possible at a high cost. The performance level of the building at R = 6 lies at CP-C for the MCE design level. Considering the building’s resilience and performance level aspects, the maximum R factor was found to be 6. This helps the stakeholder and designer in the selection of R, based on the requirements of building functionality, performance level, and resilience.